Evaluation of stress in students graduating from Occupational Therapy - Sanches, Beatriz Palombarini [UNESP]; Silva, Nilson Rogerio da [UNESP]; Silva, Meire Luci [UNESP] (Cuba Editora, 2018)
Introduction: Preparation for professional practice concurrent with personal growth of the students graduating from Occupational Therapy can trigger stress. Objective: The present research aimed to evaluate the prevalence of stress indicators in 31 students graduating from the course of occupational therapy of a public University. Method: Data were collected through a semi-structured interview for characterization of the profile of the participants and the Lipp Stress Symptoms inventory. Results: The results indicated that all were female, age of 21 years and 4 months old and single. The majority (84%) presented indicators of stress in some phases, with predominance of resistance (61.5%), followed by exhaustion (34.6%). Students have reported difficulties in meeting the training rules, reduced recreation and leisure time, emotional involvement with the patients problems. They also reported good relationsship with supervisors and students. Conclusion: The results reveal the need for emotional support as a primary factor for the students' academic and professional success.
Keywords: Students; Stress; Occupational Therapy